Comparative corrosion behaviour of stainless steels and their welds in wet-process phosphoric acid. (4th July 2021) - Chandra, K.; Singh, A. P.; Mahanti, Amrita; Kumar, Niraj; Gautam, Vicky; Kain, Vivekanand
ABSTRACT: The present study compares corrosion behaviour of three austenitic stainless steels 316L, 317L and 904L (base materials and welds) in wet-process phosphoric acid (WPA) and reagent grade phosphoric acid with impurities, e.g., Cl-, F- and SO4 2- . The corrosion study was done by performing electrochemical polarisations at 50°C followed by Tafel extrapolation. Welds always had higher corrosion rates than their respective base materials. The corrosion rates of stainless steels in plant WPA were much less compared to that in reagent grade phosphoric acid with almost similar levels of Cl −, F − and SO 4 2 − . This is due to the presence of a variety of dissolved metallic ions in WPA that reduces its corrosiveness. Among the three metallic cations (Fe 3+, Mg 2+ and Al 3+ ) examined in this study, the inhibiting action increased in the order Fe 3+  < Mg 2+  < Al 3+ . SS 904L was the most corrosion-resistant alloy in WPA followed by SS 317L and 316L.